Returning White–tailed Deer (Odocoileus virginianus) Fawns to their Mothers - Connell, Ann (Wildlife Rehabilitation Bulletin, 2005)
Determining whether a fawn needs a wildlife rehabilitator’s help is often a difficult and challenging task. Usually, this decision is made during a telephone conversation with the individual who found the fawn. The finder may have limited experience with animals and/or may have strong feelings about what course of action is best for the fawn. In addition, the rehabilitator must make this evaluation without the benefit of examining the fawn or seeing the circumstances under which the fawn was found. This can result in normal, healthy fawns being taken from their mothers to be hand–raised. A review of the author’s records of 400 white–tailed deer (Odocoileus virginianus) fawns triaged for admission over 11 years revealed that 40 percent of fawns admitted were good candidates for return to the areas in which they were found.